PrBaCo2O6-δ - Ce0.8Sm0.2O1.9 Composite Cathodes for Intermediate Temperature Solid Oxide Fuel Cells. (2nd June 2015) - Tsvetkov, Dmitry S.; Tsvetkova, Nadezhda S.; Ivanov, Ivan L.; Malyshkin, Dmitry; Sereda, Vladimir V.; Zuev, Andrey Yu.
Abstract : The single phase oxide PrBaCo2 O6-δ and composites (100-y) PrBaCo2 O6-δ - y Ce0.8 Sm0.2 O1.9 (y = 10 - 30 wt.%) were investigated as cathode materials for intermediate temperature solid oxide fuel cells. The chemical compatibility, thermal expansion, DC conductivity and electrochemical performance of these materials were studied. As a result, exchange by Pr and Sm was found between PrBaCo2 O6-δ and Ce0.8 Sm0.2 O1.9 . Cation exchange was found for both oxides not to lead to change of the crystal structure and results in slightly decreasing a and c cell parameters for Ce0.8 Sm0.2 O1.9 and PrBaCo2 O6-δ, respectively. This exchange was shown to affect significantly both thermal expansion and total conductivity of the composites studied. As a consequence, thermal expansion coefficient of the composite cathodes exceeds significantly that of the electrolyte.